Current Advances in the Biodegradation and Bioconversion of Polyethylene Terephthalate - Xinhua Qi; Wenlong Yan; Zhibei Cao; Mingzhu Ding; Yingjin Yuan (Microorganisms, 2021)
Polyethylene terephthalate (PET) is a widely used plastic that is polymerized by terephthalic acid (TPA) and ethylene glycol (EG). In recent years, PET biodegradation and bioconversion have become important in solving environmental plastic pollution. More and more PET hydrolases have been discovered and modified, which mainly act on and degrade the ester bond of PET. The monomers, TPA and EG, can be further utilized by microorganisms, entering the tricarboxylic acid cycle (TCA cycle) or being converted into high value chemicals, and finally realizing the biodegradation and bioconversion of PET. Based on synthetic biology and metabolic engineering strategies, this review summarizes the current advances in the modified PET hydrolases, engineered microbial chassis in degrading PET, bioconversion pathways of PET monomers, and artificial microbial consortia in PET biodegradation and bioconversion. Artificial microbial consortium provides novel ideas for the biodegradation and bioconversion of PET or other complex polymers. It is helpful to realize the one-step bioconversion of PET into high value chemicals.